Systematic Literature Review of The Relationship between Internal Control and Good Corporate Governance - Riyadi, Wulan; setiawan, Amelia (Finance and Business Management Journal, 2025)
This study examines more deeply about internal control and good corporate governance. The method used in this research is descriptive qualitative using systematic literature review (SLR), which is one of the methods used in research that aims to identify, evaluate, and present information related to the subject under study in order to answer existing research questions. Through the literature review, this research aims to further explore the relationship between internal control and corporate governance. This research uses data collection techniques from the Scopus database. Data collection is done through literature review by researching and monitoring documents related to internal control and GCG. The result of this study is that most of the theoretical basis used in the articles studied directly uses the core theory of their respective variables, while a small part uses agency theory, Coso internal control framework, farud triangel theory. Furthermore, based on the results of the article review, it was found that internal control has a relationship with good corporate governance. with the implementation of good internal control, it is expected that good corporate governance will be reflected